Bad moon rising - Galligan, John (Galligan, John. Bad Axe County novel., 2021)
"A record heat wave suffocates remote rural Wisconsin as the local sheriff tracks down a killer hidden in the depths of the community in this atmospheric, race-to-the-finish mystery"--